2020
DOI: 10.1140/epjc/s10052-020-8198-x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray reflection spectroscopy with Kaluza–Klein black holes

Abstract: Kaluza–Klein theory is a popular alternative theory of gravity, with both non-rotating and rotating black hole solutions known. This allows for the possibility that the theory could be observationally tested. We present a model which calculates the reflection spectrum of a black hole accretion disk system, where the black hole is described by a rotating solution of the Kaluza–Klein theory. We also use this model to analyze X-ray data from the stella-mass black hole in GRS 1915+105 and provide constraints on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…This is simply because, for the moment, efforts have been devoted to improving the model and understanding the systematic uncertainties, while less importance has been given to test specific scenarios of new physics. However, nkbb and relxill nk can be easily modified to test any black hole solution known in analytic form (see, e.g., Zhu et al 2020;Zhou et al 2021;Tripathi et al 2021c).…”
Section: Introductionmentioning
confidence: 99%
“…This is simply because, for the moment, efforts have been devoted to improving the model and understanding the systematic uncertainties, while less importance has been given to test specific scenarios of new physics. However, nkbb and relxill nk can be easily modified to test any black hole solution known in analytic form (see, e.g., Zhu et al 2020;Zhou et al 2021;Tripathi et al 2021c).…”
Section: Introductionmentioning
confidence: 99%
“…[3,15], we presented the first version of the relativistic reflection model relxill_nk, which is an extension of the relxill package developed by Thomas Dauser and Javier Garcia [23,30,31]. As nkbb, the default version of relxill_nk employs the Johannsen metric with the possible non-vanishing deformation parameter α 13 [38], but modified versions of relxill_nk have been used to test black hole solutions in conformal gravity [80,82], in Kaluza-Klein models [84], in asymptotically safe quantum gravity [83], and in Einstein-Maxwell dilaton-axion gravity [69], as in all these theories we know the analytic expression of the metric of rotating black holes. relxill_nk has also been used for testing the Weak Equivalence Principle [58], while we have not used our model for testing the atomic physics in the strong gravitational fields of black holes.…”
Section: Continuum-fitting Methodsmentioning
confidence: 99%
“…In most of our past studies, we have used the parametric black hole spacetime suggested in Johannsen (2013), which is not a solution of a specific theory of gravity but an ad hoc deformation of the Kerr metric for these kinds of studies. However, the model can also employ theoretically motivated black hole solutions (Zhou et al 2018;Zhu et al 2020;Zhou et al 2021).…”
Section: Introductionmentioning
confidence: 99%